Urban religion a historical approach to urban growth and religious change - Rüpke, Jörg 1962- (De Gruyter, 2020)
So far religion has been seen as cause for dramatic developments in the history of cities, it has contributed to the monumentalisation of centres and or has given importance to ex-centric places. Very recently, anthropologists have been discovering religion in the contemporary global city. But still awaiting historical investigation is the specific urban character of religious ideas, practices and institutions and the role of urban space shaping this very 'religion' in the course of history. The time-span from the Hellenistic age to Late Antiquity was crucial in the establishment of concepts and institutions of 'religion' and witnessed extended waves of urbanisation, Rome being central to this. In addressing this problem, this book fills a significant gap in the scholarship on urban religion across time. Taking seriously the proposition that space is condition, medium and outcome of social relations, the development of 'urban religion' in lived urban space and urban culture or urbanity offers a lens onto processes of religious change that have been neglected for the history of religion and for the study of urbanism. The key thesis is that city-space engineered the major changes that revolutionised religions